Debates on the Use of Deception in Psychology Research - Ayşe Tuna (Psikoloji Çalışmaları)
Deception is often used in scientific research as it is thought to contribute to the research process. Deception basically occurs when participants are given false or incomplete information about the purpose, content, or processes of a study. The most common types of deception involve giving false feedback about performance, including a participant in a study without their knowledge, not providing information or giving false information about the measurement tools being used, and giving false information about the roles of other people in a study. Deception is frequently used in psychology studies, especially in social psychology. Researchers use deception in subjects such as prosocial behaviors, conformity, and social dilemmas to determine participants’ instant reactions removed from social desirability and to measure behaviors in their form closest to social reality. However, deception raises questions about ethics, methodology, scientific and professional repute, and trust in researchers. The most critical ethical concern is that a researcher may cause physiological or psychological harm to participants, even if said researcher has no such intention. Discussions on methodology have focused on the ability of the use of deception to harm the participant pool and of deception to affect a participant’s future responses and reactions and on how studies that use deception are less reproducible. These debates are not only based on ethics and methodology. Deception is also thought to be able to damage trust in scientists and psychologists. Hence, researchers are recommended to use deception only as a last resort. The essential purpose of this article is to draw attention to the risks of deception and what precautions can be taken against these risks. Deception is currently considered an indispensable part of scientific research processes. Indeed, for some studies to not use deception is practically impossible based on the subject and content. In such a context, if a study that is to be conducted plans to use deception, benefit would be had in thinking about the risks of deception and in planning what can be done to eliminate risks so as to prevent any possible negative consequences.v